2014
DOI: 10.1002/chem.201402031
|View full text |Cite
|
Sign up to set email alerts
|

Reversible, Photoinduced Activation of P4 by Low‐Coordinate Main Group Compounds

Abstract: Two unique systems based on low-coordinate main group elements that activate P4 are shown to quantitatively release the phosphorus cage upon short exposure to UV light. This reactivity marks the first reversible reactivity of P4, and the germanium system can be cycled 5 times without appreciable loss in activity. Theoretical calculations reveal that the LUMO is antibonding with respect to the main group element-phosphorus bonds and bonding with respect to reforming the P4 tetrahedron, providing a rationale for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
46
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 67 publications
4
46
0
5
Order By: Relevance
“…In the 31 P{ 1 H} NMR spectrum, the four signals for 6a are observed at 98.9, 86.5, 69.7, and À17.6 ppm, those for 6b at 128.8, 78.1, 40.9, and À10.3 ppm and the signals for 6c are found at 114. 9,87.7,0.9,Supporting Information).…”
mentioning
confidence: 99%
“…In the 31 P{ 1 H} NMR spectrum, the four signals for 6a are observed at 98.9, 86.5, 69.7, and À17.6 ppm, those for 6b at 128.8, 78.1, 40.9, and À10.3 ppm and the signals for 6c are found at 114. 9,87.7,0.9,Supporting Information).…”
mentioning
confidence: 99%
“…[18,19] Ragogna et al reported the reversible, photoinduced activation of P 4 by reaction with a Ge II compound. [20] In contrast, the formation of a fully reversible equilibrium between a low-valent main-group metal complex and the corresponding intermetallic complex is without precedent.…”
mentioning
confidence: 99%
“…[35] It can also participate as al igand in organic reactions, adding to unsaturated substrateso rb eing coordinatedby carbenes. [36][37][38][39][40][41][42] Furthermore, germylene plays an important role in the facile activation of small molecules and functional groups. [43][44][45][46] Germanium compounds are also employed in the semiconductor industry.…”
Section: Introductionmentioning
confidence: 99%